(untitled) (Global Journal of Medical Research, 2023)
Background Chinese medicine CM industry has developed rapidly in recent years but the turnover rate among Chinese medicine practitioners CMPs in Hong Kong is relatively high The research on this issue is insufficient inevitably giving rise to hidden concerns regarding the development of the CM industry Purpose explores the relationship between job satisfaction work stress and organizational commitment among CMPs in Hong Kong and their turnover intention Its results provide guidance regarding the CM industry s management and suggest future research directions